Howard Watkins' Retirement from Fresno-Merced Counties Legal Services Dinner at Yen Ching Restaurant - Watkins, Howard::::::::: (1985)
Sharon Blumberg, Stephen Blumberg and Howard Watkins talking; Garrick Byers on right